Study of Excited States of Ag- Centres in Alkali Halides - Roy, R.S. (Asian Journal of Chemistry, 2010)
Two photon excitation of Ag- centres in RbCl and KCl have been presented. From the dependence of luminescence on the polarization of the exciting beams, the symmetry of the final levels could be obtained. In both the crystals, an intense band was assigned to the 1A1g → 1A1g transition. At higher energies 1A1g→1Eg and 1A1g→1E2g transitions could be identified, but their presence and intensity change in different crystals. On the high energy side of the investigated range, an intense luminescence signal arising from a two-step excitation process is observed.